Current and foreseen tungsten production in Portugal, and the need of safeguarding the access to relevant known resources - Mateus, António (2021)
The economic and strategic importance of tungsten is widely recognized, but several concerns exist on its stable future supply. Portugal is one of the main tungsten producers in Europe, having generated ≈121 kt of contained tungsten in mineral concentrates from 1910 to 2020, i.e., ≈3.3% of the global production documented for the same time period. Since the early nineties, tungsten mining in Portugal is confined to the Panasqueira deposit which accounts for 79% of the country reserves (≈5.4 kt). However, according to the performed Generalized Verhulst and Richards curve-fitting forecasts, there is a significant future potential for increasing production in Portugal due to the low (<2%) depletion rates of the remaining known tungsten resources (≈141 kt). This projected growth is not necessarily guaranteed, depending on many unpredictable economic, technological, and political factors, besides appropriate social consents. Even so, a prudent land-use planning oriented to long-term needs should avoid the sterilization of the most relevant tungsten resources so far identified in the country. These are resources of “public importance”, as objectively demonstrated with a weighed multi-dimensional (geological, economic, environmental, and social) approach. Safeguarding the access to these resources does not implicate more than ≈6% of the Portugal mainland territory. The joint interpretation of results independently gathered for tungsten production forecasts and for the definition of areas hosting tungsten resources of public importance, provides additional support to political decisions on the urgent need to reconcile mineral exploration surveys and mining with other land uses.